John Locke : de los principios del pacto social y su lucha contra el absolutismo monárquico = John Locke : on the principles of the social pact and his struggle against monarchical absolutism (2017)
This article presents some of John Locke's fundamental contributions to the consolidation of liberal thought. It begins with an introduction to the political context that animates his thought, then outlines the basic points of discord between Locke and Robert Filmer, one of his most important objects of intellectual confrontation, and then elucidates some of his main theses on the formation of the social state based on the notion of the state of nature, the critique of monarchy, and the criticism of monarchy. The article then outlines the basic points of disagreement between Locke and Robert Filmer, one of the most important objects of intellectual confrontation between them, thus elucidating some of their main theses on the formation of the social state based on the notion of the state of nature, the critique of monarchy and the division of political power with the role of property in it. The article ends with a conclusion on the principles of the social compact in Locke's theory